2012
DOI: 10.1007/s12223-012-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnostics of invasive fungal infections: an overview with emphasis on molecular approach

Abstract: Although invasive fungal diseases (IFDs) are relatively rare, they have become an increasingly common life-threatening complication in a variety of critically ill patients. Due to changes in treatment strategies, patterns of IFDs have changed substantially as well. Yeast infections have shifted toward a higher proportion of non-albicans Candida species, but their overall incidence has remained stable. In contrast, IFDs caused by molds, including particularly various species of Aspergillus, Fusarium, and Mucora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 95 publications
2
27
0
8
Order By: Relevance
“…Non-invasive methods for diagnosing invasive fungal disease (IFD) are under constant improvement. Thus, laboratory tests to detect Aspergillus galactomannan (GM), 1,3-beta-D-glucan (BG), or polymerase chain reaction (PCR)-based methods (2,14–18), although not yet standardized and validated, as well as radiological methods could facilitate the diagnosis (14). …”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive methods for diagnosing invasive fungal disease (IFD) are under constant improvement. Thus, laboratory tests to detect Aspergillus galactomannan (GM), 1,3-beta-D-glucan (BG), or polymerase chain reaction (PCR)-based methods (2,14–18), although not yet standardized and validated, as well as radiological methods could facilitate the diagnosis (14). …”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that isolates of A. terreus are associated with resistance to the antifungal drug amphothericin B, the empirical therapy for serious, invasive infections (Bašková & Buchta 2012). Furthermore, a recent study found a slight increase in invasive fungal infections due to non-albicans Candida infections, including Candida glabrata and Candida krusei in granulocytopenic and immunocompromised patients (Vazquez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged caspofungin prophylaxis in neutropenic patients has contributed to a significant increase of infections caused by C. krusei and C. glabrata (Lortholary et al 2011;Wisplinghoff et al 2014). Aspergillus fumigatus continues to be the most frequent causative agent of invasive aspergillosis however, non-fumigatus Aspergillus infections increasingly occurred (Azab et al 2015;Bašková & Buchta 2012). In particular, A. terreus has been recognised as resistant towards amphotericin B, the highly effective but also highly toxic broad-spectrum antifungal drug, with a high mortality rate for invasive infections (Blum et al 2013;Steinbach & Perfect 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations